Series Compensated Low Frequency Transformers Emulating Multipulse Rectifiers for Harmonic Current Content Minimization in Electrical Grids - Carlos A. Munoz; Carlos R. Baier; Jesus C. Hernandez; Esteban I. Marciel; Pedro E. Melin (IEEE Access, 2025)
This paper explores the use of series compensated low frequency transformers (SCLFT), operating in parallel to traditional low frequency transformers (LFT), to attenuate harmonic distortion caused by nonlinear loads in electrical networks. The proposed strategy achieves harmonic cancellation through a controlled phase shift between the SCLFT and LFT voltages, emulating the behavior of multi-pulse transformers. By integrating power converters into the LFT, the SCLFT’s operation is optimized to maximize system efficiency and implement a robust control algorithm for precise output voltage regulation. The effectiveness of the proposed approach is validated through hardware-in-the-loop (HIL) simulations and experimental testing, demonstrating a significant reduction in current harmonic distortion. These results position series-compensated SCLFTs as a viable solution for enhancing power quality in distribution grids. This technology offers a promising alternative to modernizing electrical infrastructure and paves the way for future applications in microgrid optimization and large-scale distribution systems.